E-learning system - Alampally, Swetha (Kansas State University, 2012)
E-Learning System offers online training for the employees of the company. Every company uses different technologies based on the type of work they do, products they develop and services they offer. Fresher's who are just recruited many not be familiar with the technologies the company is using or the employees already working in the company may not have required level of efficiency in those technologies. It is necessary to train all the employees of the company according to their profiles with different technologies the company uses. The main aim of the project is to create web interface for E-learning System for the employees of the company. In order to use this system the employees needs to register as member and can start using services. The registered users have more access to system and can make use of training system more efficiently then unregistered users. The registered users will have access to master library where all the materials and videos of different courses are available. The users can enroll into different levels of different courses and get trained by downloading and studying the materials available .The users can also schedule for a test for the courses and levels they are registered into. Records are created for the level and course they re passed so that admin they view them. Creating a web interface will help the employees to study easily, manage their courses efficiently and can also check their performances. It also aims for developing reports for each users in the E-Learning System so that the users can see their performances and the admin can also recommend him/her to appropriate project's based on the performance of the employee in the technologies he/she is registered into.
Keywords: Learning system; Computer Science (0984)